Aldehyde dehydrogenase in fresh primordial germ cells as a marker of cell 'stemness'. Issue 1 (1st February 2019) - Svoradová, Andrea; Vašíček, Jaromír; Ostró, Alexander; Chrenek, Peter
Summary: Chicken primordial germ cells (PGCs) are the primary pluripotent stem cell types that will differentiate towards germ cells. High aldehyde dehydrogenase (ALDH) activity is considered as a functional marker for the detection of cell 'stemness'. In our study the ALDEFLUOR™ kit was used for determination of ALDH activity in PGCs. PGCs were co-stained with diethylaminobenzaldehyde (DEAB) and ALDH and analyzed by flow cytometry. Our results showed a small cell population (8.0 ± 3.3%) upon preincubation of the cells with the specific inhibitor DEAB, however cells without inhibitor staining showed a fluorescence shift as an ALDH-positive population (70.5 ± 1.6%). These findings indicate higher expression of ALDH in PGCs and ALDH activity can therefore be used as a new functional marker for the detection of cell 'stemness' in chicken PGCs. These results may have importance for characterization of PGCs as a potential genetic resource in poultry. Further research is necessary to elucidate the role of this functional marker in these cells.